Peran Auditor Internal: Pencegahan dan Pengendalian Fraud di Bisnis Wisata Berbasis Culture Immersion - Saifudin Saifudin; Nia Luthfiana; Nirsetyo Wahdi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to find out more about the role of internal audit and the effectiveness of internal control in detecting and preventing fraud in the culture immersion-based tourism business. The method used in this research is descriptive and verification analysis method. The independent variables used in this study are Internal Audit and Internal Control Effectiveness. While the dependent variable in this study is Fraud Detection and Prevention. The population in this study were all internal auditors at the Culture Immersion-based Tourism Business Company in Semarang City. Sampling using purposive random sampling method and obtained a sample size of 353 respondents. The data analysis technique used in this research is correlation coefficient analysis, determination and hypothesis testing. The results of this study indicate that internal audit has a significant effect on fraud detection and prevention with a correlation coefficient value of 0.615 and is in the strong category. The effectiveness of internal control has a significant effect on the detection and prevention of fraud with a correlation coefficient value of 0.587 and is included in the moderate category.